PARTISIPASI MASYARAKAT DESA WISATA TERHADAP PENGELOLAAN RUMAH GODANG MALAYU KOTO SENTAJO KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI - ", Zulherian; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
In this research using descriptive qualitative research method, there is a purpose to know how the decomposition of village tourism participation in Management of Godang Malayu House in Koto Sentajo Village Sentajo Raya Sub-district Kuantan Singingi Regency. In addition, this research is also trying to identify and identify the factors driving the community in the Management of Objects of Godang Malayu Home TourismBased on the results of research that has been done there are results showing the management of Rumah Godang Malayu conducted by the community in the Village Tourism Koto Sentajo District Sentajo Raya district kuantan singing province riau very good overall. It is based on the results of interviews and observations used by the author. In addition, the management conducted by the people of Desa Wisata is supported by several factors such as the desire of the community to preserve their ancestral heritage, the building of Godang House into a tourist attraction in Koto Sentajo Tourism Village, and the belief of the people of Koto Sentajo Tourism Village will be their cultural customs.Keywords: Participation, Management, Society, Tourism Village